Material and energy flow analysis for environmental and economic impact assessment of industrial recycling routes for lithium-ion traction batteries. (1st December 2022) - Blömeke, Steffen; Scheller, Christian; Cerdas, Felipe; Thies, Christian; Hachenberger, Rolf; Gonter, Mark; Herrmann, Christoph; Spengler, Thomas S.
Abstract: Electric vehicles powered with renewable energy are considered a key technology to decarbonize the mobility sector. However, the currently used lithium-ion batteries contain environmentally harmful, scarce, and expensive materials. The recycling of spent traction batteries could mitigate the environmental impact of electric mobility by substituting primary raw materials with recovered secondary materials. Moreover, it would counter the issues related to resource scarcity and expensive materials. Therefore, the automotive industry needs to establish effective processes for taking back and recycling of batteries. While many studies have analyzed the environmental and economic impacts of lithium-ion battery recycling, the lack of transparency of the energy and material flows as well as the missing comparability between different recycling routes contradicts an in-depth life cycle engineering. Therefore, this paper aims to provide transparent material and energy flow analysis on process unit level based on physical and chemical relationships and use this to assess the environmental and economic impacts of three widely used recycling routes. The analysis focuses on pyrometallurgical, mechanical, and thermal-mechanical pretreatment, and subsequent hydrometallurgical material recovery. Furthermore, we assess the environmental and economic impacts of each recycling route. The results indicate that mechanical recycling has the highest economic benefit and avoids most environmental impacts especially due to graphite and lithium recovery. A thermal-mechanical pretreatment has environmental benefits but results in lower profit. The pyrometallurgical pretreatment results in large amounts of slag, for which the hydrometallurgical processing reduces the avoided environmental impacts significantly. The assessment results support transparent decision-making regarding the implementation and further engineering of recycling infrastructure. Highlights: Modelled battery recycling routes on process unit level based on open access data. Customizable tool to support investment decisions in recycling infrastructure. Recycling realizes profits up to 3.3 k€/t and avoids impacts up to 7.0 t CO2-eq./t. Mechanical pretreatment is economically and environmentally beneficial.